Парфюмерия и косметика в античном Херсонесе - Кадеев, В.И. (My University, 1995)
Kadeyev V. I. The Perfumery and Cosmetics in Ancient Chersoneros The paper is devoted to history of perfumery and cosmetic in ancient Chersonesus. Usuing evidences of ancient authors, archaeological and epigraphical sources, the were author showed that in Chersonesus used various means of perfumery and cosmetic from Alexandria, towns of Syria, Italia and Asia Minor. All these means of perfumery and cosmetic used in mode of life, funerals and in sacred ceremony, especially widely in the I–III A. D.